Canopy-Derived Fuels Drive Patterns of In-Fire Energy Release and Understory Plant Mortality in a Longleaf Pine (Pinus palustris) Sandhill in Northwest Florida, USA. Issue 5 (2nd September 2016) - O'Brien, Joseph J.; Loudermilk, E. Louise; Hiers, J. Kevin; Pokswinski, Scott M.; Hornsby, Benjamin; Hudak, Andrew T.; Strother, Dexter; Rowell, Eric; Bright, Benjamin C.
Abstract: Wildland fire radiant energy emission is one of the only measurements of combustion that can be made at high temporal and spatial resolutions. Furthermore, spatially and temporally explicit measurements are critical for making inferences about ecological fire effects. Although the correlation between fire frequency and plant biological diversity in frequently burned coniferous forests is well documented, the ecological mechanisms explaining this relationship remains elusive. Uncovering these mechanisms will require highly resolved, spatially explicit fire data (Loudermilk et al. 2012). Here, we describe our efforts at connecting spatial variability in fuels to fire energy release and fire effects using fine scale (1 cm 2 ) longwave infrared (LWIR) thermal imagery. We expected that the observed variability in fire radiative energy release driven by canopy-derived fuels could be the causal mechanism driving plant mortality, an important component of community dynamics. Analysis of fire radiant energy released in several experimental burns documented a close connection among patterns of fire intensity and plant mortality. Our results also confirmed the significance of cones in driving fine-scale spatial variability of fire intensity. Spatially and temporally resolved data from these techniques show promise to effectively link the combustion environment with postfire processes, remote sensing at larger scales, and wildland fire modeling efforts.